Understanding atom probe’s analytical performance for iron oxides using correlation histograms and ab initio calculations - Se-Ho Kim; Shalini Bhatt; Daniel K Schreiber; Jörg Neugebauer; Christoph Freysoldt; Baptiste Gault; Shyam Katnagallu (New Journal of Physics, 2024)
Field evaporation from ionic or covalently bonded materials often leads to the emission of molecular ions. The metastability of these molecular ions, particularly under the influence of the intense electrostatic field (10 ^10 Vm ^−1 ), makes them prone to dissociation with or without an exchange of energy amongst them. These processes can affect the analytical performance of atom probe tomography (APT). For instance, neutral molecules formed through dissociation may not be detected at all or with a time of flight no longer related to their mass, causing their loss from the analysis. Here, we evaluated the changes in the measured composition of FeO, Fe _2 O _3 and Fe _3 O _4 across a wide range of analysis conditions. Possible dissociation reactions are predicted by density-functional theory calculations considering the spin states of the molecules. The energetically favoured reactions are traced on to the multi-hit ion correlation histograms, to confirm their existence within experiments, using an automated Python-based routine. The detected reactions are carefully analyzed to reflect upon the influence of these neutrals from dissociation reactions on the performance of APT for analysing iron oxides.